Pengolahan Daur Ulang Minyak Bekas Menjadi Biodisel Untuk Sumber Energi Alternatif Di Kelurahan Karya Merdeka Kabupaten Kutai Kertanegara - Andi Sri Irtawaty; Maria Ulfah; Armin Armin (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Biodiesel is an alternative fuel that is environmentally friendly, has no effect on health, which can be used as a fuel for motor vehicles which can reduce emissions when compared to diesel oil. Biodiesel can be obtained from the recycling of used used oil mixed with chemicals in the form of methanol and NaOH with a ratio (1: 0.5: 0.001). The implementation of biodiesel can replace the function of diesel in a generator engine or dompeng engine. The 2020 PkM activities were held in Karya Merdeka Village, Kutai Kertanegara Regency. Nearly 27% of the population works as smallholders in oil palm plantations. The implementation of PkM lasted for 3 days which was attended by 25 oil palm plantation farmers. The benefit of this activity is that partners are able to recycle and implement biodiesel which is 3 times more efficient than diesel as fuel for dompeng engines (water machines used to irrigate their oil palm plantations). The goal is to save energy, that is, 3 liters of diesel can be replaced with 1 liter of biodiesel. It has been proven that biodiesel is 3 times more efficient than diesel (3 hours: 1 hour) with the same size.